MATHEMATICAL MODELING OF THE THERMAL TREATMENT PROCESS OF THE ARTICLES WITH COMPLEX INTERNAL STRUCTURE - A. N. Chichko; V. F. Sobolev; O. I. Chichko; S. G. Lihouzov; O. A. Sachek (Литьë и металлургия)
Influence of pressure of gas phase, irradiation, physical and mechanical and electro-physical ways of influence on intensification of diffused processes of oxides deoxidation is examined.